Comparison of “Amicus and COBE Spectra” for autologous peripheral blood stem cell harvest: An Indian experience - Rasika Dhawan Setia; Satyam Arora; Anil Handoo; Dharma Choudhary; Sajeev Kumar Sharma; Tina Dadu; Divya Doval; Meenu Kapoor; Shalu Bajaj; Virendra Bachchas (Global Journal of Transfusion Medicine, 2017)
Background: Adequate collection of peripheral stem cells from the patients depends on the disease condition, efficient mobilization and the equipment used for PBSC harvest. COBE Spectra has been the major platform for collecting these PBSC for more than 2 decades. Now with introduction of PBSC harvest option with Amicus cell separators (which was used primarily for plateletpheresis) in India, it is worth while comparing both the platforms for stem cells collections. Materials and Methods: Our study is a retrospective analysis of autologous PBSC harvest procedures done at our centre. The study included the data of autologous PBSC collections from January 2015 to June 2016. Total 61 patients underwent 85 autologous PBSC harvests for both haematological and non haematological indications. Results: Out 61 patients, 40 patients collected their target number of cell in a single harvest, 18 patient required dual harvests and 3 patients required three consecutive days of harvest. Pre-Apheresis WBC, platelets and CD45/CD34 cell counts were comparable. COBE Spectra collects significantly higher product volume and higher number of platelets in the apheresis product. Whereas WBC counts of the product, total CD45/CD34 cell dose and collection efficiency (CE2) and collection ratio (CR) were comparable on both the platforms. Conclusions: Amicus took more time to harvest the anticipated number of cells in the graft as well as COBE Spectra resulted in higher platelets loss during the process of cell collection. Our analysis is first of its kind from Indian subcontinent and indicates that with gradual phasing out of COBE spectra from the market Amicus offers a comparative platform for PBSC harvest.